2016
DOI: 10.1007/s00394-016-1305-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and dietary patterns: a systematic review and meta-analysis of observational studies

Abstract: The results from cross-sectional studies showed that a prudent/healthy pattern is associated with a lower prevalence of MetS, whereas a Western/unhealthy is associated with an increased risk for MetS. Additional prospective studies are needed to confirm the association between dietary patterns and MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
131
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(155 citation statements)
references
References 89 publications
17
131
0
7
Order By: Relevance
“…Induction of MetS in rodents through HCHF diet has been well-established by previous studies [28,29]. It mimics the dietary habit of the Western population with high consumption of saturated fat and wide use of refined sugar as sweeteners in beverages [36]. In this study, HCHF diet for 16 weeks successfully induced MetS by causing central obesity, high blood pressure, and hypertriglyceridemia in rats, which fulfilled at least three criteria put forward by the harmonized definitions of MetS [1].…”
Section: Discussionmentioning
confidence: 60%
“…Induction of MetS in rodents through HCHF diet has been well-established by previous studies [28,29]. It mimics the dietary habit of the Western population with high consumption of saturated fat and wide use of refined sugar as sweeteners in beverages [36]. In this study, HCHF diet for 16 weeks successfully induced MetS by causing central obesity, high blood pressure, and hypertriglyceridemia in rats, which fulfilled at least three criteria put forward by the harmonized definitions of MetS [1].…”
Section: Discussionmentioning
confidence: 60%
“…Trolox or Vc solution (5-100 µg/mL) were served as positive controls. The results were expressed as the percentage of inhibition in the following Equation (1).…”
Section: Phenolic Compositions Analysis By Hplc-esi-hr-qtof-ms/msmentioning
confidence: 99%
“…Nowadays, incidences of metabolic syndrome-related diseases have rapidly increased all over the world, such as oxidative damage, diabetes, obesity, hypertension, and cardiovascular disease [1]. Food nutritionists have revealed that oxidative stress and high-calorie diets was closely related to the development of chronic disease [2].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance (IR) is the main pathologic characteristic of MetS and the most accepted unifying theory explaining the pathophysiology of the disease. 1 In the search for improved and novel therapeutic strategies, microRNAs (miRNAs) have drawn attention as potential targets due to their regulatory role on gene networks involved in metabolism, including lipid and glucose homeostasis. 2 Mounting evidence suggests that circulating miRNAs are involved in the regulation of obesity, diabetes, and MetS, but existing studies have yielded inconclusive results.…”
Section: Introductionmentioning
confidence: 99%